Aplikasi Agenda Kegiatan Pada BPSDMP Komunikasi Dan Informatika Banjarmasin Berbasis Web - Herpendi Herpendi; Resni Habibah (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
Balai Pengembangan Sumber Daya Manusia dan Penelitian (BPSDMP) Komunikasi dan Informatika Banjarmasin is an agency that focuses on research and development activities in the field of communication and informatics and has three organizational structures namely Administrative Subdivision, Human Resources Development Section, Research Section for Communication and Information Technology. BPSDMP Komunikasi dan Informatika Banjarmasin has routine activities every year, namely ICT Literacy activities, Research results seminar, SKKNI-based national certification, Digital talent, and Meetings. The recording of the activity agenda and reporting on the results of the activities that are currently running are still done manually and simply. To overcome this problem then built an expected Web Based Activity Agenda Application can simplify the work of Administration Subdivision, HR Development Section, Research and Communication Section of Information and Communication Technology because it's computerized to print report results and make it easier if you want to see the data of activities that have been managed at the same time can find out if there are activities that are forgotten and have not been implemented. Application Activity AgendaService is made using a programming language PHP, HTML, CSS and Javascript. And designed to use Entity Relationship Diagram, Data Flow Diagram and Flowchart.